2018
DOI: 10.1103/physreva.98.022133
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs in multiparty Bell-inequality violations in qubit networks

Abstract: Two overlapping bipartite binary Bell inequalities cannot be simultaneously violated as this would contradict the usual no-signalling principle. This property is known as monogamy of Bell inequality violations and generally Bell monogamy relations refer to trade-offs between simultaneous violations of multiple inequalities. It turns out that multipartite Bell inequalities admit weaker forms of monogamies that allow for violations of a few inequalities at once. Here we systematically study monogamy relations be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…The linearisations in section 3 can also be read as inequalities identifying parts of the boundary of the set of quantum correlations. The results reveal that part of the boundary of the quantum set is flat, a characteristic that has previously been remarked upon in [35,37]. It may be interesting to study how our results generalise to Bell experiments involving more parties.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The linearisations in section 3 can also be read as inequalities identifying parts of the boundary of the set of quantum correlations. The results reveal that part of the boundary of the quantum set is flat, a characteristic that has previously been remarked upon in [35,37]. It may be interesting to study how our results generalise to Bell experiments involving more parties.…”
Section: Resultssupporting
confidence: 75%
“…For readers familiar with both, it may seem natural to ask whether the security of the HBB scheme can be proved device independently, i.e., without assuming that the participants' devices are necessarily measuring σ x and σ y . There have indeed been proposals to design a device-independent secret-sharing protocol based on the GHZ-paradox or other correlations arising from GHZ states [20,34,35]. However, we found that the HBB scheme is completely insecure from a deviceindependent point of view.…”
Section: Overviewmentioning
confidence: 77%
“…A more natural family of such functions was proposed by Slofstra [60], but these require a large number of measurement settings on each side. On the other hand, a simple example was recently found in the tripartite p3 -2 -2q scenario by Ramanathan and Mironowicz [61]. In this section we give an example in the bipartite scenario p2 -3 -2q and two additional examples in the p3 -2 -2q scenario.…”
Section: Nonlocal Faces Of Positive Dimensionmentioning
confidence: 79%
“…Generally Bell monogamy relations refer to trade-offs between simultaneous violations of multiple inequalities. The genuine multipartite nonlocality, as evidenced by a generalized Svetlichny inequality, does exhibit monogamy property [25]. There is a complementarity relation between dichotomic observables leading to the monogamy of Bell inequality violations [26].…”
Section: Introductionmentioning
confidence: 99%